STUDI KONDISI KECEPATAN OPERASI PADA RUAS JALAN DI DALAM LINGKUNGAN KAMPUS UNIVERSITAS TADULAKO - Batti, Joy Fredi (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
Improvement of roads within the Campus of Tadulako university will have an impact on increasing theoperating speed of traffic. When the speed of operation that occurs well above design speedoperating then the problem of safety of road users in a campus of Tadulako University will be a seriousproblem that the operating speed in the campus need to be evaluated. The purpose of this study wasto evaluate the operational speed conditions that occur on roads within the Campus of TadulakoUniversity.Travel time data collection of traffic on a road segment length on the campus of Tadulako Universityhas been done in the month of December in 2011 for two days. The travel time data used inestimating the speed of traffic data. Determination of speed of operation is based on the 85percentile. Determination of the operating speed based on the Lamm R. et. al. In 1999.The results of research to get several conclusions as follows: roads are good criteria for R1, R3, R4, R5,R6, R7 and R8, fair criteria for R2. The study also found that there is a 50.0% rate exceed V= 35 km/h onroad segment 3 (R3), 45.0% on road segment 5 (R5), 40.0% on each road segment 2 and 6 (R2, R6),20.0% on road segment 1 (R1). The recommended type of speed control is rumble strip, speed humpsand bumps.